2004
DOI: 10.1080/02724980343000666
|View full text |Cite
|
Sign up to set email alerts
|

Movement Trajectories in the Presence of a Distracting Stimulus: Evidence for a Response Activation Model of Selective Reaching

Abstract: Consistent with action-based theories of attention, the presence of a nontarget stimulus in the environment has been shown to alter the characteristics of goal-directed movements. Specifically, it has been reported that movement trajectories veer away from (Howard & Tipper, 1997) or towards (Welsh, Elliott, & Weeks, 1999) the location of a nontarget stimulus. The purpose of the experiments reported in this paper was to test a response activation model of selective reaching conceived to account for these variab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
123
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(147 citation statements)
references
References 35 publications
22
123
2
Order By: Relevance
“…If more than one object is attended, multiple action plans are generated (Cisek & Kalaska, 2005), and the actual movement may represent a mixture between these action plans if there was not sufficient time to inhibit the movement plans to the wrong locations. With little time to inhibit conflicting movement plans, the final response represents a mixture between a response to the target and a response to the distractor, which is what was observed in the present and in previous studies (Buetti & Kerzel, 2009;Scherbaum, Dshemuchadse, Fischer, & Goschke, 2010;Welsh, 2011;Welsh & Elliott, 2004).…”
Section: Discussionsupporting
confidence: 84%
“…If more than one object is attended, multiple action plans are generated (Cisek & Kalaska, 2005), and the actual movement may represent a mixture between these action plans if there was not sufficient time to inhibit the movement plans to the wrong locations. With little time to inhibit conflicting movement plans, the final response represents a mixture between a response to the target and a response to the distractor, which is what was observed in the present and in previous studies (Buetti & Kerzel, 2009;Scherbaum, Dshemuchadse, Fischer, & Goschke, 2010;Welsh, 2011;Welsh & Elliott, 2004).…”
Section: Discussionsupporting
confidence: 84%
“…To this aim, the cognitive system has an inhibitory mechanism that, in normal conditions, rules out the outputs to distractors, in order to achieve subjects' goals (e.g. Welsh and Elliott 2004). This mechanism has been proposed to be efficient but not entirely effective (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…An analogy can perhaps be found in the literature on the role of visual nontarget objects (that are not necessarily physical obstacles) in reaching and grasping tasks Tipper, Howard, Jackson, 1997;Welsh, Elliott, Weeks, 1999). These studies have reported that visual non-target objects that surround the target influence the trajectory of the target-directed hand movement by either veering away from Tipper et al, 1997) or towards the visual non-target object (Welsh et al, 1999;Welsh, Elliott, 2004). To explain these effects, the response activation model (Welsh, Elliott, 2004; for an alternative explanation, see Howard, Tripper, 1997) proposes that prior to the execution of an action attention is distributed throughout the environment.…”
Section: The Penalty Kicker's Perceptions Are Implicitly Influenced Bmentioning
confidence: 76%
“…In fact, Welsh and Elliott (2004) observed with neutral stimuli that if the visual non-target object was present before the onset of action, the inhibitory processes had sufficient time to de-activate the associated action response processes. In the current experiment, the goalkeeper is also presented well before the kicker's run-up, however, in all likelihood the goalkeeper is a salient rather than a neutral visual stimulus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation